University and Globalization: Changes and Challenges (2017)
The universities, having gone through an unprecedented development in terms of number and coverage in the second half of the past century, are now confronted with new social and technological phenomena linked to globalization, which obliges them to radically reinvent themselves under penalty of being relegated in the competitive world of supply of education. Phenomena such as relocation of their users, advances in learning neurosciences, competition in terms of teacher quality, educational and virtual media development, and transnational market of educational supply, among others, will test the university’s capacity to create and integrate new ways to develop its essential duties of teaching, researching and continuing education. On the basis of the Black swan theory developed by Nassim Taleb, this article presents some cultural and institutional pedagogy elements that might help universities to respond to the new conditions under which they will have to operate in a globalized world.